Settlement of Inherited Land Conflicts for Sale Unilaterally - Renda Adi Wibowo; Riska Apriliana; Esti Harjanti Candrarini (PT FORMOSA CENDEKIA GLOBAL, 2022)
Conflict is a conflict or dispute, a process carried out by people or groups of people to fulfill their goals by opposing the opposing party accompanied by threats and violence. The problem of land disputes between inheritance is currently a scourge because it is thought that the inheritance can provide welfare for those who receive the inheritance. The existing and applicable inheritance law in Indonesia is still not a legal unification. The form and system of inheritance law is closely related to the form of society and the nature of kinship. The research method used is a normative juridical approach, namely a legal research that uses secondary legal sources, carried out by emphasizing and adhering to the juridical aspects. Nature of Inheritance Law The existing and applicable inheritance law in Indonesia is still not a legal unification. The form and system of inheritance law is closely related to the form of society and the nature of kinship. Meanwhile, the family system in Indonesian society is based on the system of drawing a lineage, which is basically known to have three types of hereditary systems.